Numerical simulation of thermal processes in the elements of MHD-pumps used for transferring liquid metals - Golotina, Lyudmila Aleksandrovna; Glot, Irina Olegovna; Khripchenko, Stanislav Yurievich; Shardakov, Igor Nikolaevich (Computational Continuum Mechanics, 2013)
The paper is devoted to numerical simulation of the non-stationary thermophysical processes occurring in the liquid metal feed pipe of MHD pumps. The non-stationary heat-conduction problem is formulated and solved numerically by the finite element method using ANSYS software. The results of numerical simulations are compared with the previously obtained experimental data. A series of numerical computations have been carried out to estimate the influence of different parameters on the process of pipe heating, which allowed us to determine the optimal parameters ensuring effective operation of MHD-pumps.
Keywords: MHD-pump; liquid metal; flow; thermal conductivity; electric heating; numerical solution; physical experiment